Viral Load And Cd4+ among Hiv/Aids Patients Receiving Antiretroviral Therapy In Jayawijaya District, Papua Province, Indonesia - Mirna Widiyanti; Moch. Irfan Hadi; Setyo Adiningsih; Evi Iriani Natalia; Dedi Ananta Purba (Folia Medica Indonesiana, 2022)
Hightlight:• Clinical conditions, CD4+ cell counts, and the viral copies number in the blood for AIDS/HIV were given antiretroviral therapy. • The profile of CD4+ levels and plasma viral load in HIV patients receiving antiretroviral therapy • The lower CD4+ cell counts and higher viral loads happen in HIV-infected’s men.